Feedback stabilization for a chemostat with delayed output - Gonzalo Robledo (Mathematical Biosciences and Engineering)
We apply basic tools of control theory toa chemostat model that describes the growth of onespecies of microorganisms that consume a limiting substrate. Under theassumption that available measurements of the model have fixed delay$τ>0$, we design a family of feedback control laws with the objective of stabilizing the limiting substrate concentration in a fixedlevel. Effectiveness of this control problem is equivalent to global attractivity of a family of differential delay equations. We obtain sufficient conditions (upper bound for delay $τ>0$ andproperties of the feedback control) ensuring global attractivity and localstability. Illustrative examples are included.